KULTIVASI SPIRODELA POLYRHIZA DENGAN PENAMBAHAN ELISITOR KITOSAN UNTUK MENINGKATKAN PRODUKSI FLAVONOID SEBAGAI SENYAWA ANTIOKSIDAN - Dwi Septiani, Dinda
Spirodela polyrhiza is a species of duckweed known as an aquatic plant with a very fast growth rate. Until now, the use of S. polyrhiza, especially in Indonesia, is still limited to its use as a mixture of feed and bioremediator in polluted water bodies. On the other hand, the content of jlavonoid compounds makes S. polyrhiza potential to be used in the health sector, especially because of its antioxidant activity. Elicitation has been recognized as one of the effective methods to increase the production of secondary metabolites from plants. Chitosan is a natural elicitor that is known to trigger plant defense responses by increasing the production of phytoalexin compounds such as flavonoids. In this study, elicitation was carried out at the cultivation stage of S. polyrhiza with variations in the concentration of chitosan O (control), 50 mg/L, I 00 mg/L, and 200 mg/L. The results showed that S. polyrhiza cultivated with the addition of chitosan had a slower growth rate than control plants with the lowest value of 0.162 day1 for a concentration of 200 mg/L chitosan. The concentration of chitosan at I 00 mg/L showed the best elicitation efficiency compared to other variations, where the total phenolic content (136.27 ± 11.56 mg GAE/g extract) increased by 2.66 times compared to the total phenolic content of control plants (51.28 ± 0.4 mg GAE/g extract). The same thing was also seen in the total flavonoid content, where the total flavonoid at a concentration of JOO mg/L chitosan (89.2 ± 3.42 mg QE/g extract) increased by 3 times compared to the total flavonoid content of control plants (29.78 ± 2.76 mg QE/g extract). In addition, the extract of S. polyrhiza at various concentrations of chitosan I 00 mg/L showed the highest antioxidant activity with an IC50 value of 42.86 ppm. Overall, increasing the production of phenolic and flavonoid compounds as a result of elicitation using chitosan is one of the first steps in optimizing the use ofsustainable resources.